2016
DOI: 10.1186/s12889-016-3069-y
|View full text |Cite|
|
Sign up to set email alerts
|

Tailored message interventions versus typical messages for increasing participation in colorectal cancer screening among a non-adherent population: A randomized controlled trial

Abstract: BackgroundThe purpose of this study was to examine the effectiveness and cost-efficiency of a tailored message intervention compared with a non-tailored message intervention for increasing colorectal cancer (CRC) screening rates among a non-adherent population, in a community-based client reminder program.MethodsAfter a baseline survey for psychological segmentation, 2140 eligible individuals were randomly assigned either to a group with a tailored matched-message condition (N = 356), a group with a non-tailor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…The majority of studies focused on breast cancer, 17,20,28-30,33,34,36,37,39,41 followed by cervical cancer, 20-23,31,32,35,41,42 colorectal cancer, 25-27 oral cancer, 38,40 and gastric cancer. 27 The countries in which the studies were conducted included Japan, 20,21,26,28,41 Malaysia, 22,23,40,42 Korea, 27,37,39 Taiwan, 17,31,32 Israel, 25,36 Lebanon, 19,29 Singapore, 30,33 India, 34 Turkey, 35 and Iran 38 (Fig 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies focused on breast cancer, 17,20,28-30,33,34,36,37,39,41 followed by cervical cancer, 20-23,31,32,35,41,42 colorectal cancer, 25-27 oral cancer, 38,40 and gastric cancer. 27 The countries in which the studies were conducted included Japan, 20,21,26,28,41 Malaysia, 22,23,40,42 Korea, 27,37,39 Taiwan, 17,31,32 Israel, 25,36 Lebanon, 19,29 Singapore, 30,33 India, 34 Turkey, 35 and Iran 38 (Fig 2).…”
Section: Resultsmentioning
confidence: 99%
“…37 A study focusing on colorectal and gastric cancer targeted men only, 27 and four studies (either targeting colorectal or oral cancer) included both men and women. 25,26,38,40 The age range of included participants differed among studies and the type of cancer addressed (ie, cervical cancer awareness studies generally targeted women 20 years of age and older, breast cancer awareness studies targeted those 30 years of age and older, and some included women 50 years of age and older (with one exception 37 ). Colorectal and gastric cancer studies included participants between 46 and 74 years of age, and oral cancer studies did not use age as an exclusion criterion.…”
Section: Resultsmentioning
confidence: 99%
“…Since the announcement of the cancer control plan to increase the participation rate in cancer screening programs by the Japanese government [6], various promotion strategies including sending invitation letters and conducting awareness campaigns have been attempted [9,19]. Although these strategies have been implemented nationwide, they had sadly not achieved the goal of increasing the participation rate to date.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate of CRC is the third highest of all cancers for men (42.9 ppm) and the highest for women (34.6 ppm) [1]. The CRC screening program, which uses the fecal occult blood test (FOBT), is a recognized effective approach, and is, thus, reinforced by the public sector to reduce incidence and mortality rates [2]. Despite the expected effectiveness of the preventive approach, CRC screening is yet to be fully implemented, and fails to be recognized as important by the recipients, with uptake levels remaining at low levels.…”
Section: Aim and Objectivesmentioning
confidence: 99%
“…"; and (iii) "can belief be affected by an educational campaign?" This approach was also applied to a precedent study conducted by the city of Hachioji in 2016 [2]. It revealed that a message for loss-avoidance based on prospect theory was more effective than a normal one.…”
Section: Nudge Theory Towards Behavioral Changesmentioning
confidence: 99%